2003
DOI: 10.1002/mrc.1214
|View full text |Cite
|
Sign up to set email alerts
|

Complete assignments of 1H and 13C NMR resonances of oleanolic acid, 18α‐oleanolic acid, ursolic acid and their 11‐oxo derivatives

Abstract: One way to increase the rate of an electrochemical process is to increase the area of the interface between the electrode and the electrolyte. A novel polymer electrode, with a very high effective surface area and a nanometer‐scale continuous conducting network that extends into a large volume, is presented and its preparation from a commercially available aqueous dispersion of a conducting polymer described. An application to supercapacitors is detailed, as a demonstration of the properties that are a consequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
249
0
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 443 publications
(285 citation statements)
references
References 9 publications
30
249
0
6
Order By: Relevance
“…The non-polar fraction (soluble in hexane) afforded no purified substance after several steps, but the last sub-fraction in the chromatographic fractionation of the semipolar fraction (soluble in EtOAc) yielded a pure substance after washings with hexane/EtOAc that was identified as ursolic acid (1, Figure 1) based on the NMR data (Table 2S, Figures 1S-11S), which were in agreement with the data published in the literature for the same substance. 50,51 The production of ursolic acid (1) by M. tomentosa is per se interesting, since this substance presents pharmacological activities, and some assays have demonstrated that it is far less toxic to human beings than the available commercial insecticides to control L. coffeella in coffee fields. 52 Furthermore, it reduced the oviposition of this insect (Table 1), showing potential for use in the development of new products to control this pest.…”
Section: Resultsmentioning
confidence: 99%
“…The non-polar fraction (soluble in hexane) afforded no purified substance after several steps, but the last sub-fraction in the chromatographic fractionation of the semipolar fraction (soluble in EtOAc) yielded a pure substance after washings with hexane/EtOAc that was identified as ursolic acid (1, Figure 1) based on the NMR data (Table 2S, Figures 1S-11S), which were in agreement with the data published in the literature for the same substance. 50,51 The production of ursolic acid (1) by M. tomentosa is per se interesting, since this substance presents pharmacological activities, and some assays have demonstrated that it is far less toxic to human beings than the available commercial insecticides to control L. coffeella in coffee fields. 52 Furthermore, it reduced the oviposition of this insect (Table 1), showing potential for use in the development of new products to control this pest.…”
Section: Resultsmentioning
confidence: 99%
“…In a second study, the hexane and EtOAc extracts of the roots of the specimen collected in the central Brazilian cerrado were submitted to several chromatographic columns, which eventually lead to the identification of the triterpenes α-amyrin, β-amyrin, 26 oleanolic acid, 27 glochidonol, 28 and the mixture of stigmasterol, β-sitosterol and campesterol. 29,30 The new quinone diterpene derivative was identified by 1 H NMR and 2D NMR experiments, such as HSQC, HMBC, and 1D NOE (Table 1), as well high-resolution mass spectrometry.…”
Section: Resultsmentioning
confidence: 99%
“…31 All the compounds isolated from the roots of the second specimen were identified through comparison of their spectral data with the literature. [26][27][28][29][30] …”
Section: Resultsmentioning
confidence: 99%
“…These compounds were identified as kaempferol (Carotenuto et al, 1996) and lupeol (Ali et al, 2007) respectively. SA-6 was isolated from the n-butanol fraction and was identified as 18-α-oleanolic acid based on the spectral information (Seebacher et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The butanol fraction (10.0 g) was separated over silica gel column with a solvent system of CHCl 3 :MeOH: H 2 O (9:4:0.5-3:5:0.5) as the eluent to give five fractions, among them the major fraction was purified by repeated CC using methanol as eluent, to give SA-6. Characterization of isolated compounds was done by comparing the spectral data in the literature (Carotenuto et al, 1996;Ali et al, 2007;Seebacher et al, 2003).…”
Section: Isolation Proceduresmentioning
confidence: 99%